2015
DOI: 10.1080/15459624.2015.1043057
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Combustion Aerosol Particles Through Filters of NIOSH-Certified Filtering Facepiece Respirators (FFRs)

Abstract: Filtering facepiece respirators (FFRs) are commonly worn by first responders, first receivers, and other exposed groups to protect against exposure to airborne particles, including those originated by combustion. Most of these FFRs are NIOSH-certified (e.g., N95-type) based on the performance testing of their filters against charge-equilibrated aerosol challenges, e.g., NaCl. However, it has not been examined if the filtration data obtained with the NaCl-challenged FFR filters adequately represent the protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…The latter result indicates that the filter material used in the test mask displays oil resistance. As such, the test mask would be expected to provide filtration efficiency for combustion products (40) in addition to the efficiency demonstrated for sodium chloride (a surrogate for allergens and pollutants such as PM 2.5 ). As discussed above for filtration of infectious agents, comparative testing of N95 facepiece respirators and surgical masks has shown that surgical masks are less effective for filtration of sodium chloride aerosols (41).…”
Section: Discussionmentioning
confidence: 99%
“…The latter result indicates that the filter material used in the test mask displays oil resistance. As such, the test mask would be expected to provide filtration efficiency for combustion products (40) in addition to the efficiency demonstrated for sodium chloride (a surrogate for allergens and pollutants such as PM 2.5 ). As discussed above for filtration of infectious agents, comparative testing of N95 facepiece respirators and surgical masks has shown that surgical masks are less effective for filtration of sodium chloride aerosols (41).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a diesel exhaust challenge, rather than sodium chloride, provides a scenario that is closer to real-world exposures, particularly near busy roads, where people are more likely to wear masks. Gao et al 27 found that N95 filters did not perform as well compared with R95 or P95 filters when exposed to combustion source aerosol (wood, paper and plastic) compared with NaCl, although all these filters did filter at least 95% of the aerosol.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mechanisms that may explain the differences in penetration of combustion and NaCl particles through the tested filters include the formation of loose agglomerates on the fibers, neutralization or reduction of charge occurring on fiber due to deposition of oppositely charged particles, as well as chemical reaction (Barrett and Rousseau, 1998). The above mechanisms have been considered in our recent studies (Grinshpun et al, , 2014Gao et al, 2015), which reported similar differences in collecting combustion and NaCl particles by an N95 NIOSH-certified respirator filter. …”
Section: Data Interpretationmentioning
confidence: 78%